Gaya Hidup Mahasiswa: Sebuah Studi Mengenai Analisis Pengaruh Financial Knowledge Terhadap Sikap Hedonisme di Kalangan Mahasiswa - Maliha, Aisyah; Septiani, Fauzia; Azilla, Vika Hayatal; Muttaqin, Walady Ersa; Rozak, Rama Wijaya Abdul; Mulyani, Heni (ANTHOR: Education and Learning Journal, 2023)
This study aims to see how the relationship between finansial literacy and financial knowledge on the style of hedonism among students. The method used is descriptive qualitative by distributing questionnaires via google form to 100 students throughout Indonesia. The results showed that financial literacy and financial knowledge can affect financial management, while technology and the environment are supporting factors for the financial literacy process of students. Thus, hedonistic behaviour is not always influenced by the student's living environment, this is because literacy and financial knowledge affect financial management more than technology and student living environment which are only supporting factors for student finansial management.